Comparison of Metarhizium isolates for biocontrol of helicoverpa armigera (Lepidoptera : Noctuidae) in chickpea - Kulkarni, Shuklangi A.; Ghormade, Vandana; Kulkarni, Girish; Kapoor, Manisha; Chavan, Santosh B.; Rajendran, Armugam; Patil, Sanjay K.; Shouche, Yogesh; Deshpande, Mukund V. (Biocontrol Science and Technology, 2008)
Metarhizium isolates from soil (53) and insect hosts (10) were evaluated for extracellular production of cuticle degrading enzyme (CDE) activities such as chitinase, chitin deacetylase (CDA), chitosanase, protease and lipase. Regression analysis demonstrated the relation of CDE activities with Helicoverpa armigera mortality. On basis of this relation, ten isolates were selected for further evaluation. Subsequently, based on LT(50) of the 10 isolates towards H. armigera, five isolates were selected. Out of these five isolates, three were selected on the basis of higher conidia production (60-75 g/kg rice), faster sedimentation time (ST(50)) (2.3-2.65 h in 0.1% (w/v) Tween 80) and lower LC(50) (1.4- 5.7 x 10(3) conidia/mL) against H. armigera. Finally, three Metarhizium isolates were selected for the molecular fingerprinting using ITS sequencing and RAPD patterning. All three isolates, M34412, M34311 and M81123, showed comparable RAPD patterns with a 935G primer. These were further evaluated for their field performance against H. armigera in a chickpea crop. The percent efficacies with the three Metarhizium isolates were from 65 to 72%, which was comparable to the chemical insecticide, endosulfan (74%).
Keywords: appressorium formation; chitin deacetylase; chitinase; chitosanase; Helicoverpa armigera; Lipase; Metarhizium anisopliae; Protease

Development of mycoinsecticide for the control of insect pests: comparative evaluation of metarhizium isolates to identify strains for commercialization - Deshpande, Mukund V.; Kulkarni, Shuklangi A.; Ghormade, Vandana; Kapoor, Manisha; Chavan, Santosh B.; Kulkarni, Grish; Shouche, Yogesh (New Biotechnology, 2009)